Review of stable and transitional status techniques for troubleshooting in distribution systems (2010)
Fault location on distribution systems has become an important issue due to the negative impact due to perception economy and quality issues that it is implied in a low continuity service. There are many techniques and strategies proposed  for  this problem, however,  it  is not clear which one  is  the best. This paper presents a  review of  some techniques that use a steady state analysis and techniques that use transient state analysis to locate short-circuit faults  with low fault resistance in radial systems. The main conclusion is that, due to the commitment with the precisión of the techniques, a combination of some strategies is needed for a real system implementation.